2016
DOI: 10.1590/1808-1657000542014
|View full text |Cite
|
Sign up to set email alerts
|

Frequência de ovinos soropositivos para lentivírus de pequenos ruminantes no município de Colinas do Tocantins, estado do Tocantins, Brasil

Abstract: RESUMO: Maedi-Visna (MV) é uma enfermidade causada por lentivírus de pequenos ruminantes com evolução crônica e em grande parte dos casos sinais clínicos inaparentes. O diagnóstico da doença é baseado em sinais clínicos e dados epidemiológicos, sendo a imunodifusão em gel de ágar (IDGA) o método padrão para a detecção sorológica de anticorpos contra o lentivírus. Sabendo que o estado do Tocantins possui potencial para o desenvolvimento da ovinocultura e que grande parte dos produtores de Colinas do Tocantins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Although there are no reports in the literature that associate these factors with MV, all risk factors in this study are probably associated with less technified properties, which is contrary to what has been described by other authors (Illius et al, 2020). However, this type of breeding is mainly associated with poor nutritional and sanitary management, which are predisposing factors for viral infection In the present study, no statistically significant differences were observed in sex, age, and breed, which was also reported by other authors (Mazzinghy et al, 2016;Larruskain & Jugo, 2013).…”
Section: Resultscontrasting
confidence: 96%
See 1 more Smart Citation
“…Although there are no reports in the literature that associate these factors with MV, all risk factors in this study are probably associated with less technified properties, which is contrary to what has been described by other authors (Illius et al, 2020). However, this type of breeding is mainly associated with poor nutritional and sanitary management, which are predisposing factors for viral infection In the present study, no statistically significant differences were observed in sex, age, and breed, which was also reported by other authors (Mazzinghy et al, 2016;Larruskain & Jugo, 2013).…”
Section: Resultscontrasting
confidence: 96%
“…The positivity of anti-MVV antibodies observed in the present study (1.4%) can be classified as very low (1% to 9%) (Reina et al, 2009) as in other Brazilian regions investigated using AGID. Mazzinghy et al (2016) found 1.62% (6/369) of seropositive individuals in Tocantins. In Bahia, Martinez et al (2011) observed 0.3-0.5% and Pinheiro et al (2018) 1.56% (13/831) of seropositive individuals.…”
Section: Resultsmentioning
confidence: 95%
“…One way out of this understanding is that the manifested clinical signs are not pathognomonic, since other diseases may show the same signs, such as aspiration pneumonia or bacterial origin, arthritis by Mycoplasma spp, mastitis of bacterial origin and lymphadenitis caused by Corynebacterium pseudotuberculosis (PRITCHARD;MCCONNELL, 2007) Another thing to be considered is the requirement of non-reagent animals for lentivirus by the creators when purchasing them. This fact was confirmed by Mazzinghy et al (2016), since the achievement of seronegative results and with animal transit guide is an effective preventive measure against the introduction of new cases in the state of Tocantins, place of work, since that, regions in increase stage of its herds end up purchasing a large amount of animals, subject to greater risk of purchasing animals with diseases, as well as facilitating the tracing of the animal and knowing with precision their origin. However, the search for negative herds is a very wide bias, a consequence of a lack of communication between breeders and technical assistance and by the few laboratories that carry out this test, being mostly available in the form of agar gel immunodiffusion kits.…”
Section: Discussionmentioning
confidence: 86%